Incidence, Impact, and Causes of Presenteeism in Nurses at a Tertiary Care Hospital - Arshad, Madeha; Huma, Zille; Elahi Bux, Nusrat; Fatima, Arooj (Biological and Clinical Sciences Research Journal, 2025)
Presenteeism, defined as attending work despite illness or other conditions that hinder productivity, is a growing concern in healthcare settings. It can negatively impact patient care, increase the risk of medical errors, and contribute to burnout among nurses. Understanding the prevalence, causes, and consequences of presenteeism in nurses is crucial for designing effective workplace policies and interventions. Objective: To assess the incidence, impact, and causes of presenteeism among nurses working at a tertiary care hospital. Methodology: A cross-sectional study was conducted in the Nursing Department of Medicare Hospital, Multan, from January 2024 to January 2025. Nurses employed for at least the past 12 months were included. Data were collected using a structured questionnaire divided into four sections: demographic details, the Sickness Presenteeism Questionnaire, work productivity loss assessment, and causes of presenteeism. Statistical analysis was performed using SPSS Version 25, with significance at p<0.05. Results: The mean presenteeism score was 2.68 ± 0.88, with 95% of nurses experiencing presenteeism in the last six months. Significant differences were observed across age groups (t = -2.28, p = 0.03), work experience (t = -5.03, p = 0.00), and marital status (t = -2.09, p < 0.05). The primary causes of presenteeism included excessive workload (65%), insufficient leave policies (65%), conscientiousness (60%), and financial constraints (55%). Conclusion: The study revealed a high incidence of presenteeism among Pakistani nurses, significantly associated with age, social status, and work experience. Key contributing factors included excessive workload, lack of adequate leave, financial pressures, and a sense of professional responsibility. Addressing these challenges through improved staffing, better leave policies, and workplace wellness initiatives may help mitigate presenteeism and enhance nurse well-being and patient safety.